The Influence of Leadership and Work Culture on Employee Discipline at PT. ARA - Raden Djoko Goenawan; Anoesyirwan Moein; Alex Zami (International Journal of Economics, Management and Accounting (IJEMA), 2023)
The purpose of this study is to know and analyze the influence of leadership on work discipline, to know and analyze the influence of work culture on work discipline and to know and analyze the influence of leadership and work culture on work discipline at PT. ARA. The approach used in this study is an associative approach. The population in this study is the overall employees of PT. ARA numbered 538 people and the sample used in this study was the entire population of 84 people using the slovin formula. The data collection technique in this study used questionnaires. Data analysis techniques in this study use Classical Assumption Test, Multiple Regression, t Test and F Test, and MinDetermination Coefficient. Data processing in this study used the SPSS software program (version 24.00). It is partially known that leadership has a positive and significant influence on the performance of work discipline. It is partially known that work culture has a positive and significant influence on work discipline. It is simultaneously known that leadership and work culture have a significant positive influence on work discipline at PT. ARA.